Weight change in the first 2 months of a lifestyle intervention predicts weight changes 8 years later. (July 2015) - Unick, Jessica L.; Neiberg, Rebecca H.; Hogan, Patricia E.; Cheskin, Lawrence J.; Dutton, Gareth R.; Jeffery, Robert; Nelson, Julie A.; Pi‐Sunyer, Xavier; West, Delia Smith; Wing, Rena R.; the Look AHEAD Research Group
<x xml:space="preserve">Abstract</x> Objective Examine the relationship between 1‐ and 2‐month weight loss (WL) and 8‐year WL among participants enrolled in a lifestyle intervention. Methods 2, 290 Look AHEAD participants (BMI: 35.65 ± 5.93 kg/m2) with type 2 diabetes received an intensive behavioral WL intervention. Results 1‐ and 2‐month WL were associated with yearly WL through Year 8 (P's < 0.0001). At Month 1, participants losing 2‐4% and >4% had 1.62 (95% CI: 1.32, 1.98) and 2.79 (95% CI: 2.21, 3.52) times higher odds of achieving ≥5% WL at Year 4 and 1.28 (95% CI: 1.05, 1.58) and 1.77 (95% CI: 1.40, 2.24) times higher odds of achieving ≥5% WL at Year 8, compared to those losing <2% initially. At Month 2, 3‐6% WL resulted in greater odds of achieving ≥5% WL at Year 4 (OR = 1.85; CI: 1.48, 2.32), and >6% WL resulted in the greatest odds of achieving ≥5% WL at Year 4 (OR = 3.85; CI: 3.05, 4.88) and Year 8 (OR = 2.28; CI: 1.81, 2.89), compared to those losing <3%. Differences in adherence between WL categories were observed as early as Month 2. Conclusions 1‐ and 2‐month WL was associated with 8‐year WL. Future studies should examine whether alternative treatment strategies can be employed to improve treatment outcomes among those with low initial WL.